SISTEM INFORMASI AKADEMIK PENILAIAN BERBASIS WEB PADA SMA MANDIRI BALARAJA - KAB. TANGERANG - Eko Yulianto; Ahmad Yani; Nurajijah Nurajijah (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2018)
SMA Mandiri Balaraja - Kab. Tangerang continues to strive to offset the development of education to compete and reliable. The assessment system is still manual and not computerized. This causes difficulties in the assessment process, as many require files to be recorded. Academic information system of web-based value processing answer the problem, because it can be accessed online anywhere and anytime with the internet network. The model used in this research is waterfall method supported by programming language PHP, HTML and MySQL database.